Effects of Aerobic Endurance Training vs HIIT on Energy Intake, Macronutrient Intake, and VO2Max Level on Fitness Centre Participants - Mury Kuswari; Nazhif Gifari; Aditya Himarwan (Inspiree)
The  purpose  of  the study Nowadays, there are many people who participate in fitness centre to maintain their health and fitness. There are many ways to increase VO2Max, an indicator of cardiorespiratory fitness, two of many were High-Intensity Interval Training (HIIT) and traditional aerobic endurance training. In other hand exercise in any type of way required extra energy, resulting in increased energy and macronutrient intake. Was to analyse the effects of HIIT vs. Aerobic Endurance Exercise on energy intake, macronutrient intake, and VO2Max of fitness centre participants in Depok..